E-leadership in Social Change: A New Paradigm in Bangladesh - Tabassum, Maliha; Kundu, Priyanka (Nepalese Journal of Management Science and Research, 2019)
We are living in a technology driven world where this society, is the most interconnected society ever. Bangladesh, despite having low income, little access to internet and literacy rates, is one of the heaviest social media user countries. According to Global Digital Statshot of Q2 report of 2017, Dhaka, the capital city of Bangladesh, became second Facebook using prone city where youth are the main user. This has made a shift in traditional leadership style where digital platform brought up fresh opportunity to create an effective leadership genre, E-leadership. E-leadership is using digital platform especially social media as leaders virtually influence and instruct followers to achieve a common goal. Despite having significant influence among city youths, insufficient attention was given to this newly emerged leadership style in social media research. Considering this research gap, this study aims to investigate how social media is used as a platform by E-leaders to practice their leadership and how E-leaders perceive the media for social change. The study would analyze two E-leadership based initiatives, 1) Ten Minutes’ School (YouTube) and 2) Youth Opportunities Bangladesh (Facebook) where selected contents will be analyzed alongside in depth interviewing of two E-leaders who are the entrepreneurs of two initiatives. Transformational leadership theory is considered as the framework for conceptualizing the context of this study and analyzing collected data.